Kontribusi Lembaga Pendidikan dan Dakwah Haji Halim terhadap Pengembangan Masyarakat Islam di Palembang - Mohd Aji Isnaini (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2017)
Community development comes out for many problems faced by humans nowadays. It grows as a social movement, progressive consciousness from some international community serving the needs and prosperity of the feeble. The variety of people faced by da’i will guide them to the relevant concepts of Islamic preach with its various objects which demands the messenger professionalism with multi knowledge and people typology. Prophet Muhammad SAW, has given the direction to think as a preach methodology empirically by saying “Khatibu al-nas ‘ala qadri ‘uqulihim.” Talk on the level of your audiences thinking. The way people think reflects on the system of life, likes the way they have their faith, culture and civilization. Thing that would like to be discussed is preach institution Haji Halim which is out of sight. There is no single work spot on the contribution of this institution. It is not known in detail what it is happened. In fact, Haji Halim is originally come from Palemng, South Sumatera, and now has been well known that he has a big influence in Palembang and surrounds.